O cronista Dr. Semana, leitor de jornais - Azevedo, Silvia Maria [UNESP] (Associação Brasileira de Literatura Comparada, 2024)
A novelty in the field of pictorial art in the 19th century, caricature was consolidated in Brazil with the Semana Ilustrada (RJ, 1869-1876), an illustrated magazine in which Machado de Assis, under the pseudonym Dr. Semana, signed the “Badaladas”. By assuming the role of a newspaper reader, the columnist made use of journalistic text mediation in the creation of satirical chronicles, which allows them to be approached from the concept of caricature by Gombrich, for whom caricatural art is guided by the principle of equivalence rather than similarity to reality.

Novidade no campo da arte pictórica no século XIX, a caricatura consolidou-se no Brasil com a Semana Ilustrada (RJ, 1869-1876), revista a qual Machado de Assis, sob o pseudônimo Dr. Semana, assinou as “Badaladas”. Ao assumir o papel de leitor de jornais, o cronista valeu-se da mediação do texto jornalístico na elaboração das crônicas satíricas, o que permite aproximá-las da concepção de caricatura de Gombrich, para quem a arte caricatural é pautada pelo princípio da equivalência e não da semelhança em relação à realidade.
The columnist Dr. Semana, reader of newspapers
Keywords: Semana Ilustrada; Dr. Semana; satirical chronicle; caricature; Semana Ilustrada; Dr. Semana; crônica satírica; caricatura